Seroprevalence of Toxoplasma gondii in Schizophrenic Patients in Iraq using ELISA test - AL-Maamuri, Suhair; AL-Shanawi, Fawzia; Melconian, Alice (Iraqi Journal of Science, 2023)
Toxoplasmosis is a widespread infection of great importance, and that the disease does not show any clinical specific signs . this study was performed on 200 patients with schizophrenia were collected from :Al-Rashad Teaching Hospitals and 100 healthy individuals, considered as control group, the samples were collected during the period of December 2012 until the end of February, 2013. Antibodies against T. gondii parasite in the serum were detected by using latex agglutination test (LAT) and showed a percentage of positive antibodies in schizophrenic patients and healthy individuals (control) 143(71.5%) and 45( 45%) respectively.While using Enzyme Linked Immunosorbent Assay (ELISA) the positive blood sera in LAT test of the schizophrenic patients showed 114(79.7%) IgG against T. gondii compared to 33(73.3%) of the healthy individuals with no significant differences. Also detection of IgM in the sera of the schizophrenic patients showed 6(4.19%) compared to0 (0 %) of healthy individuals with significant differences between them.